2019
DOI: 10.1002/jcb.28806
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LASP2 inhibits the proliferation, migration, and invasion of cervical cancer cells

Abstract: LIM and SH3 protein 2 (LASP2) belongs to nebulin family. It has been proven that LASP2 is involved in several cancers; however, its role in cervical cancer is unclear. Herein, we showed that LASP2 was highly expressed in cervical cancer tissues and cell lines. To knockdown LASP2 in cervical cancer cells, small interfering RNAs (siRNAs) targeting LASP2 (si‐LASP2) were used. We found that cell proliferation, migration/invasion were markedly reduced after si‐LASP2 transfection. A significant increase in E‐cadheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…However, the role of NEBL in cancer is complex. NEBL is a member of nebulin family of actin binding proteins (Zhang and Zhang, 2019). Zhang et.al found that NEBL promoted cancer cell proliferation, migration and invasion in cervical cancer by regulating PI3K/Akt pathway (Zhang and Zhang, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of NEBL in cancer is complex. NEBL is a member of nebulin family of actin binding proteins (Zhang and Zhang, 2019). Zhang et.al found that NEBL promoted cancer cell proliferation, migration and invasion in cervical cancer by regulating PI3K/Akt pathway (Zhang and Zhang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…NEBL is a member of nebulin family of actin binding proteins (Zhang and Zhang, 2019). Zhang et.al found that NEBL promoted cancer cell proliferation, migration and invasion in cervical cancer by regulating PI3K/Akt pathway (Zhang and Zhang, 2019). On the contrary, upregulation of NEBL inhibited cancer cell migration and invasion and reversed TGF-β-induced EMT in prostate cancer (Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…qPCR analysis for the Bcl-2 and DLEU2 genes and miR-15a was performed using an aliquot of first-strand cDNA as the template in a 20- µ l reaction system containing 10 µ l 2X SYBR premixed buffer (Roche, Shanghai, China), 2 µ l forward and reverse primers. The primers were as follows: Bcl-2 forward, 5′-CTGCACCTGACGCCCTTCACC-3′ and reverse, 5′-CACATGACCCCACCGAACTCAAAGA-3′; DLEU2 forward, 5′-TCTGGAGAACAGCCTCACTTC-3 and reverse, 5′-TGCT GAGCTAAGTAGAGGTCTC-3′ ( 18 ); β-actin forward, 5′-CTGGCTCCTAGCACCATGAAGAT-3′ and reverse, 5′-GGTGGACAGTGAGGCCAGGAT-3′ ( 19 ); U6 forward, 5′-CTCGCTTCGGCAGCACATA-3′ and reverse, 5′-CAGTGCAGGGTCCGAGGTA-3′; miR-15a forward, 5′-CGCCTAGCAGCACATAATGG-3′ and reverse, 5′-AGTGCAGGGTCCGAGGTAT-3′ ( 20 ). The PCR amplification process was as follows: 5 min denaturation at 95°C followed by 40 cycles at 95°C for 20 sec, 58°C for 15 sec, and 72°C for 15 sec (ABI StepOnePlus, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, SRC tyrosine kinase is closely related to tumor cell growth, metastasis, cell signal transduction and angiogenesis. This target has been recognized as an important anti-tumor target [48], and is also a research hotspot of tumor treatment [49,50]. Previous studies [51][52][53] have confirmed that Src kinase inhibitor PP2 can inhibit the proliferation, migration and invasion of lung cancer cells by inhibiting the activity of the enzyme.…”
Section: Discussionmentioning
confidence: 99%